2017
DOI: 10.15761/rri.1000117
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of hashimoto thyroiditis to Graves’ disease

Abstract: Hashimoto's thyroiditis and Graves' disease are thyroid-specific autoimmune disorders with distinct pathological mechanism. Clinical presentation and histopathological features also vary greatly in these disorders. Sequential conversation from Hashimoto's thyroiditis (HT) to Graves' disease (GD) has been rarely reported throughout the world. Herein, we report a woman with history of HT, who then developed GD requiring total thyroidectomy. By reporting this case, we hope to raise awareness about this phenomenon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Ultrasound examination after the relapse of Basedow's disease revealed that the thyroid gland was not very hypervascular compared to that at the onset of the disease Hashimoto's disease rather than Basedow's disease [9,10]. There are a few reports showing the transformation of Hashimoto's thyroiditis to Basedow's disease [11][12][13][14][15], but in many of these reports such arguments are based on clinical and laboratory features.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound examination after the relapse of Basedow's disease revealed that the thyroid gland was not very hypervascular compared to that at the onset of the disease Hashimoto's disease rather than Basedow's disease [9,10]. There are a few reports showing the transformation of Hashimoto's thyroiditis to Basedow's disease [11][12][13][14][15], but in many of these reports such arguments are based on clinical and laboratory features.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the progression of the thyroid immune diseases is similar to a pendulum clock dance, where they can develop from one form to another in the same patient and in both directions (11). HT and GD are the two main forms of a spectrum of thyroid immunological diseases (12). Although the conversion of HT to GD is a rare phenomenon and its mechanism is still unclear, a few cases were reported in the medical literature.…”
Section: Discussionmentioning
confidence: 99%
“…Although the conversion of HT to GD is a rare phenomenon and its mechanism is still unclear, a few cases were reported in the medical literature. Table 1 provides a summary of some cases (2,4,(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate that the pathogenesis of hyperthyroidism in these patients is similar to HT, and it could be named autoimmune hyperthyroidism rather than classical GD. What is more, recently some reports suggest a conversion of GD to HT [22, 23] and vice versa [24].…”
Section: Discussionmentioning
confidence: 99%